Green synthesis of silver, gold and silver/gold bimetallic nanoparticles using the Gloriosa superba leaf extract and their antibacterial and antibiofilm activities. (December 2016) - Gopinath, Kasi; Kumaraguru, Shanmugasundaram; Bhakyaraj, Kasi; Mohan, Subramanian; Venkatesh, Kunga Sukumaran; Esakkirajan, Masanam; Kaleeswarran, Periyannan; Alharbi, Naiyf S.; Kadaikunnan, Shine; Govindarajan, Marimuthu; Benelli, Giovanni; Arumugam, Ayyakannu
Abstract: The green fabrication of metal nanoparticles using botanical extracts is gaining increasing research attention in nanotechnology, since it does not require high energy inputs or the production of highly toxic chemical byproducts. Here, silver (Ag), gold (Au) and their bimetallic (Ag/Au) nanoparticles (NPs) were green synthesized using the Gloriosa superba aqueous leaf extract. Metal NPs were studied by spectroscopic (UV–visible spectroscopy, fluorescence spectroscopy, FT-IR spectroscopy, XRD and EDX) and microscopic (AFM and TEM) analysis. AFM and TEM showed that Ag and Au NPs had triangular and spherical morphologies, with an average size of 20 nm. Bimetallic Ag/Au NPs showed spherical shapes with an average size of 10 nm. Ag and Ag/Au bimetallic NPs showed high antibacterial and antibiofilm activities towards Gram-positive and Gram-negative bacteria. Overall, the proposed synthesis route of Ag, Au and Ag/Au bimetallic NPs can be exploited by the pharmaceutical industry to develop drugs effective in the fight against microbic infections. Graphical abstract: Highlights: We fabricated Ag, Au and Ag/Au nanoparticles using Gloriosa superba extract. NPs were characterized using a wide array of biophysical methods. Ag and Au NPs showed triangular and spherical shapes, with mean size of 20 nm. Ag and Ag/Au bimetallic NPs showed high antibacterial and antibiofilm activity. Au NPs did not show any toxic activity.